1986
DOI: 10.1525/aa.1986.88.1.02a00110
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Consequences of Female Contribution to Subsistence

Abstract: There is a growing body of literature on sexual division of labor and its relation to social o r g a n i z a t i o n ( M u r d o c k 1949;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 23 publications
0
34
0
1
Order By: Relevance
“…Schlegel and Barry (1986) compared values in 185 non-industrial societies. They found that in societies in which women made substantial contributions to the food-based economy, people were more tolerant of premarital sexual permissiveness-for both boys and girls.…”
Section: Social Psychological (Biopsychosocial) Perspectivesmentioning
confidence: 99%
“…Schlegel and Barry (1986) compared values in 185 non-industrial societies. They found that in societies in which women made substantial contributions to the food-based economy, people were more tolerant of premarital sexual permissiveness-for both boys and girls.…”
Section: Social Psychological (Biopsychosocial) Perspectivesmentioning
confidence: 99%
“…Schlegel & Barry (11,113) find further relationships between female subsistence contributions and the value placed on girls, premarital permissiveness, and other variables.…”
Section: Intensity Of Production and The Division Of Labormentioning
confidence: 92%
“…As noted above, however, our patriarchy result should be corroborated with larger samples, phylogenetic comparative methods, and perhaps refined data on patriarchy. Variation in sex differences in sports participation also might be illuminated with more refined measures of female power, such as control of resources Barry, 1986;Yanca & Low, 2004) or quantitative estimates of the number of kin and female allies present (Hill et al, 2011).…”
Section: Variation Across Societiesmentioning
confidence: 99%